Kokkang Art Studio : Structure and Function of Passing Down Potentials of Caricature Through Generation - Beniarso, Mundin; Triyanto, Triyanto; Utomo, Udi (Catharsis, 2018)
Caricature is a picture which is distorted to send a satirical or funny message. It is portrayed in a printed media with a function of becoming a social control or a sword of opinion. This research has several objectives. First, it discusses the structure and function of KOKKANG art studio. Second, it reviews the learning of intergenerational caricature of KOKKANG art studio in Kaliwungu, Kendal. This research used descriptive qualitative design assisted with the approach from the theory of modern sociology. The supporting data were collected from observation, interview, and documentation. Triangulation of sources and data were used to validate the findings. Then, the data were analysed under the steps of data reduction, presentation, and conclusion (verification). There are some points from the findings of the research. First, the functional structure of KOKKANG art studio is interrelated to other structure. Some function in each position of the organization has worked as their job description. Thus, it impacts the inheritance of drawing caricature which is done by the education section of the organization. Second, the non-formal learning pattern done by the studio is friendly and familiar, thereby it produces the cadres of cartoonists which can maintain their existence. Based on the findings, there are some suggestions to be proposed. First, KOKKANG studio should actively promote and regenerate to keep the existence of it in the future. Second, the teenagers in Kaliwungu should actively participate in the part of the community by joining or following the agenda. Third, local government should be involved in supporting the studio whether morally or materially to continue its existence.